2011
DOI: 10.1007/s00213-011-2173-z
|View full text |Cite|
|
Sign up to set email alerts
|

Behavioral economics of food reinforcement and the effects of prefeeding, extinction, and eticlopride in dopamine D2 receptor mutant mice

Abstract: Rationale Several studies have investigated the reinforcing effects of food in genetically-engineered mice lacking dopamine D2 receptors (DA D2Rs), however behavioral-economic analyses quantifying reinforcement have not been conducted. Objective The role of DA D2Rs in food reinforcement was examined by comparing responding under various fixed-ratio (FR) schedules of reinforcement, and effects of extinction, satiation, and the DA D2R antagonist eticlopride, in mice with and without genetic deletions of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
(52 reference statements)
3
13
0
Order By: Relevance
“…Haloperidol also influenced responses emitted. In the vehicle condition, the peak responses were in the medium FR range (50 – 90), which replicates other behavioral economic studies (Rasmussen et al, 2010; Soto et al, 2011; Rasmussen et al, 2012). For most FRs, especially those in that range, an injection of haloperidol reduced the number of responses emitted.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Haloperidol also influenced responses emitted. In the vehicle condition, the peak responses were in the medium FR range (50 – 90), which replicates other behavioral economic studies (Rasmussen et al, 2010; Soto et al, 2011; Rasmussen et al, 2012). For most FRs, especially those in that range, an injection of haloperidol reduced the number of responses emitted.…”
Section: Discussionsupporting
confidence: 87%
“…Another study by Soto et al (2011) supports D 2 involvement in effort-based food consumption. Here, genetic variations in D 2 receptor densities affected demand for food in three different mouse strains: a D 2 knockout lean mouse (KO), which lacked D 2 receptors, a heterozygous (HET) mouse and a wildtype (WT) mouse: the latter two had typical levels of D 2 receptors and served as controls.…”
Section: Introductionmentioning
confidence: 81%
“…Sessions initially began with the subject placed in the chamber, and with the houselight and LEDs on. Training was generally as described previously (Soto et al, 2011). Under final conditions, the FR value was five, the post-reinforcer timeout was 10 s and the timeout at the start of the session was five min.…”
Section: Methodsmentioning
confidence: 99%
“…Hursh and Silberberg (2008) have shown that the two measures, α and Q 0 , represent independent aspects of reinforcement with Q 0 affected by variables such as magnitude of reinforcement and α affected by variables such as level of deprivation and economic conditions under which the reinforcer is obtained. Soto et al (2011) used demand curves to compare reinforcing effectiveness of food and found that the curves decreased more steeply in DA D 2 R KO compared with WT or heterozygote subjects indicating a lower reinforcing effectiveness of food with D 2 R deletion. The present study extends that assessment to the DA D 3 R and D 4 R subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Katz and Soto (Johns Hopkins University). Some of these results were previously published [11]. Future studies will focus on cannabinoid systems and CB1 receptors using genetically engineered knockout and wildtype littermates.…”
mentioning
confidence: 81%